Estimation of C-Peptide, HSP60 and Anti-GAD Antibody Levels in Type 1 Diabetes Mellitus - Duha T. Khalaf (Journal of Global Pharma Technology, 2018)
Type 1 diabetes, previously known as insulin-dependent diabetes or juvenile diabetes, is caused by the destruction of beta cells responsible for insulin secretion in the pancreas through a process in which T-cells play a central role. The study was conducted on 56 patients with type 1 diabetes, whose mean ages (12.68 ± 3.33) years, and 20 healthy people, as control group for comparison purposes at the National Center for Diabetes and Endocrine Research (Al-Mustansiriyah University) from February 2017 until July 2017. Venous blood samples were collected from patients and healthy individuals to evaluate the levels of Fasting Serum Glucose FSG, C-peptide, Heat Shock Protein 60 (HSP60) and Anti-Glutamic Acid Decarboxylase (anti-GAD) antibodies. The results of the study showed a highly significant increase in the level of FSG, HPS60 and Anti-GAD antibodies in patients compared to the control group (P <0.001),while C-peptide showed a highly significant decrease in patients when compared with the control group (p <0.001).Keywords: T1D – C-Peptide – HSP60 – Anti-GAD.